ACCLMesh: curvature‐based navigation mesh generation. (12th May 2016) - Berseth, Glen; Kapadia, Mubbasir; Faloutsos, Petros
Abstract: The proposed method computes a navigation mesh for arbitrary and dynamic 3D environments based on curvature and is robust and efficient. This method addresses a number of known limitations in state‐of‐the‐art techniques to produce navigation meshes that are tightly coupled to the original geometry, incorporate geometric details that are crucial for movement decisions, can robustly handle complex surfaces and can efficiently repair the navigation mesh to accommodate dynamically changing environments. The method is integrated into a standard navigation and collision avoidance system to simulate thousands of agents on complex 3D surfaces in real time. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The maturity of algorithms for pathfinding and local collision avoidance has paved the way for autonomous navigation and agent‐based systems to prosper in complex environments. However, current solutions for computing a suitable representation of the navigable areas of these environments, which enables efficient pathfinding and collision avoidance, cannot handle unstructured, arbitrarily complex 3D environments. The proposed method computes a navigation mesh for arbitrary and dynamic 3D environments based on curvature.